The effect of company size and leverage on earnings management practices in food and beverage sub-sector companies on the Indonesian stock exchange - Maya Kartika Handayani (Institute of Accounting Research and Novation (IARN), 2021)
The objective of the research is to find out empirical evidence of the influence of firm size and leverage on earnings management. The population of this study were listed foods and beverages companies in the Indonesia Stock Exchange. The sample was determined based on the following criteria: (a) the annual report ended December 31, and (b) available and published on the Indonesia Stock Exchange website during the research period. There were 12 companies complying with the criteria. Data analysis was carried out in terms of pool cross-section covering the annual financial report during 2004-2008. The research hypotheses were tested using multiple regression analysis. Firm size was measured by logarithm, leverage was measured by debt to equity ratio and earnings management was estimated by Utami model.